O engenho criativo da Mussuca : desenvolvimento e cultura no campo negro de Laranjeiras, Sergipe - Lima, Marcelo Rangel (2019)
Based on the historical structural method, this study problematizes relations between development and cultural expressions in the city of Laranjeiras, with emphasis on a community named Mussuca, known for the uniqueness of its rites and celebrations, in which African references and matrices stand out in the cultural diversity of Sergipe. Based on the historical process that shaped local development, marked by the sugar economy and the exploitation of slave labor, we identified how rebellions and strategies of cultural resistance shaped by yearnings for freedom and ties of solidarity established spaces for action in the slave society, consolidating symbolic practices that stand out against white and European standards. The historicity of territorial occupation at the confluence of Sergipe and Cotinguiba rivers by the descendant population of enslaved women and men shows the formation of a remnant quilombos community, but it is through traditional celebrations that Mussuca consolidates its own cultural identity. The insertion of their communal cultural manifestations in official events and celebrations breaks the isolation of blacks from the outskirts of the city and promotes their participation in artistic, social and political circles. Based on the thoughts of Celso Furtado and the propositions of intergovernmental organizations, as well as on historical research and anthropological reflections, we present argumentations over those processes and local agents of transformation, emphasizing their creative capacities as inducers of visibility and social integration.